GENDER DYNAMICS IN OSSETIA IN THE XIXth – EARLY XXth CENTURY - Gutieva, El'vira Samil'evna (History, Archeology and Ethnography of the Caucasus, 2019)
The article attempts to determine the role of women in the traditional Ossetian society. Without taking into consideration the gender aspects of various branches of social and humanitarian studies, a full-fledged research of a number of pressing issues of science is impossible. The subordinate position of women in a family was determined by time, customs, traditions, which were indisputable at that time. The transformation of gender consciousness in Ossetia was accompanied by changes in the family and gender norms of society. New research tasks allow us to consider the transformation of gender stereotypes in various ethnocultural environments in diachrony, comparing not only the differences of a particular culture, but also the degree of their changes over time, the significance of social, political and other factors affecting this process.The historical gender and division of labor is a cultural solution to the problem of combining technology with the vital needs of society as a self-organizing system. Representatives of the socio-political thought of Ossetia advocated the development of professional female education, teaching girls more than useful crafts, which contributed to the expansion of the female socio-cultural space. The development of female educational institutions and their growing popularity were largely due to the post-reform modernization of Ossetian society. The real dynamics of social development led to intensive integration, and stimulated educational processes, including the expansion of the female school system. One of the major factors in the development of the female education was also the attitude of Ossetian society to it.The striving towards education in Ossetia has become a nationwide movement in which all segments of society have participated. The values of education, including the female one, entered the public consciousness of the Ossetians. The author of the article analyzes the contribution of the first Ossetian female-playwright Roza Kochisova and the first Ossetian ballerina Aurora Gazdanova to the development of gender transformations in Ossetia in the 19th and early 20th centuries.
Keywords: gender; woman; Ossetia; traditional society; transformation; culture; dramaturgy; ballet; Rosa Kochisova; Aurora Gazdanova.